Increased Growth of Pakcoy Mustard Plants With AB Mix and Growth Regulators in Axis Hydroponics System: Peningkatan Pertumbuhan Tanaman Sawi Pakcoy Dengan AB Mix dan Zat Pengatur Tumbuh Pada Hidroponik Sistem Sumbu - Miftakhurrohmat, A.; Abror, M. (Procedia of Social Sciences and Humanities, 2022)
The purpose of this study was to determine how to increase the production of mustard pakchoy on the provision of AB mix nutrition and growth regulators in the hydroponic system of the axis. This research was conducted in January – March 2022. This study used a factorial randomized block design (RAK), namely the first factor was the dose of AB mix nutrition which consisted of three levels, namely 100%, 75%, 50% and 25%. The second factor is the concentration of growth regulators 1cc, 2cc and 3 cc so as to produce 12 treatment combinations. Each treatment was repeated 3 times so as to produce 36 experimental units. Observation variables include plant height, stem diameter, number of leaves, wet weight and dry weight of the plant. The results showed that the provision of AB-Mix Nutrients and Growth Regulating Substances could increase the growth of Pakchoy Mustard Plants.